(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2022)
Fellow pilgrims in the academe and the never-ending educational journey. May the peace of the heavens be with you. Union Christian College has adopted as its theme this school year, “Heralding the Full Life: Our Educational Agenda.” This thematic emphasis revisits the raison d’etre of our College, a former mission school committed to bringing the good news of the full life to the communities in the region during the turn of the 20th century. A century and twelve years later, and after our harrowing experience of the global pandemic, the vision of full life, more than ever, continues to inform, inspire, and nourish our perspectives on what whole-person education is about. It is about the full life. The full life is our agenda. The vision of a full life is an age-old quest for humanity. This is present in the dreaming and cosmo-visioning of ancient communities, in the imaginations of every know religion, in the philosophical reflection of sages and philosophers, and in the many social and scientific revolutions that transpired and are happening in our contemporary world. In the Judaeo-Christian tradition, the full life is the realization of shalom, and shalom is the sum of interhuman justice, material satisfaction, and spiritual fulfillment However universal the vision of the full life is, not all agree on how the full life should be distributed and appropriated. This is the sad story of humanity. In a popular religious metaphor, the human aspired to become like God and cut the cord that binds him or her to his/her siblings. Humanity, as a result, was divided between the strong and the weak, the haves and the have-nots, the powerful and the powerless, the rich and the poor. The full life was then appropriated to mean the state of living within the upper tip of a social pyramid beyond the access and experience of the mass of humanity. This became the order of life. What is true in the human commune is also true in the wider ecological order. The human put himself/herself atop the ecological pyramid and had his/her dominion destroy the web of life leaving the earth mortally wounded and gasping for breath. It is primarily due to this ecological injustice that we are experiencing these days the fury of climate change and global warming. We have been, for two years, forcibly quarantined because of the global pandemic. It was the worst of times for those who are not in the zones of war. But what further pushed us to cynicism, fear, and despair is the infodemic that is at its most toxic during this period. This infodemic is vicious in that truth and science became the immediate casualty. We are seeing today how pseudo-science is invading us and contributing to our mismanagement of the crises, thus unnecessarily prolonging our difficult situation. The lament of academics like us is that we have spent years of our lives studying, teaching, researching, writing, publishing, and sharing ideas, practices, and critical information in the service of our shared emancipatory agenda only to see the products of our labors and our contributions unappreciated if not summarily dismissed as simply a buzz among the deafening buzzes of swarms of glorified “Maritesses.” It is extremely disheartening when the lifetime work and commitment of researchers-scholars are casually distorted, twisted, and erased while lies and half-truths are peddled as truth on social media. This has become more disturbing and enraging in recent years when even the learned and highly credentialed consent to this all-out assault and undermining of well-researched and well-established historical facts. It is the irony of all ironies that, in the age of social media when communication, information, and transportation technologies are revolutionizing toward the zenith of our “fourth industrial” imagination, truth and real, deep connectedness are the casualties. “Lies laced with anger and hate” as the popular saying goes, are "spreading faster than boring facts." Contrary to the common perception that the technological revolution and its social media aspect promote social connection and cohesion, indicators point to fragmentation in the global commune. What is happening on social media is happening in our day-to-day lives. The violence that we witness online is being replicated in real-world violence even as real violence is being played out in social media. This is a vicious cycle that goes with whatever good is heralded by current technological and scientific innovations. In the regime of the “new normal,” the highly contagious virus of half-truths and lies gets “normalized” and becomes an organic part of us. Truth is the casualty when lies and half-truths get normalized. The researcher scholars’ fear of people becoming impervious to facts has come to pass. “Without truth,” says the Nobel Peace Prize awardee, Maria Ressa, “we cannot have trust. [And] without trust, we have no shared reality, and it becomes impossible to deal with our world’s existential problems.” In this situation, whatever are our experiments on democratic reordering crumble from within and popular authoritarian regimes fill in the vacuum. Indicators pointing to this reality are alarming and we do not need to go far to sense this. When not addressed in due time and lies and half-truths become the staple in the regime of the “new normal,” our society’s very foundation crumbles bottom up. We were witnesses to the resilience and radical hoping of the mass of our population, but resilience is not enough. Our resilience must translate into hope, and our hope into action. We need to metamorphose into something new. We are now at the end of our cocooning. For some two years, we were forced to cocoon, and cocoon we did. In the life-rite of butterflies and moths, cocooning means transformation: the shedding-off of our old selves and the embracing of a new one. We were in a liminal zone and just now, on the threshold of something new. Not quite the new normal but post-new normal. The new normal is wanting. In the education setting, the new normal is simply re-tooling and re-skilling in the service of the social mess that was the old normal. In contrast, the post-new normal perspective pushes for the more transformative agenda of our educational work - in achieving something beyond the limited imaginations of the architects of our social madness. Should not this be the paradigm of our research work? To look for ways to overcome the social madness that contributed to our being on edge of civilizational collapse. We need to know how to extricate ourselves from the social madness that is increasingly crippling us. We need science in every step we make and take - toward our complete physical, social, and spiritual healing. Mass paranoia, mass hypnosis, and religious agitation must give way to a more scientific understanding and rational discernment of the signs of the times. The relationship between our academic work or research work to the social vision of Shalom or the full life is like a jigsaw puzzle. We and our work are some of these jigsaw pieces. We may not see the immediate relevance of our work, but it is part of a grand design towards affecting the full life. The vision of SHALOM may have been lifted from religious reason, specifically, from the Judaeo-Christian scriptures, but this religious reason, using the “translation” method of both John Rawls and Jurgen Habermas, can mean sustainable development. What has been enumerated by the UN as its 2030 Agenda for Sustainable Development included the following: No Poverty Zero hunger Good health and well-being Quality education Gender equality Clean water and sanitation Affordable and clean energy Decent work and economic growth Industry, innovation, and infrastructure Reduced inequalities Sustainable cities and communities Responsible consumption and production Climate action Life below water Life on land Peace, justice, and strong institutions Partnerships for the goals These may be temporal appropriations of the grandiose vision of the biblical shalom but are strategic to the survival and flourishing of human and planetary life. They also negate the realities that we are experiencing in the present under the regimes of both the old and new normal. Our ACSCU hopes to contribute to addressing these 17 SDGs through research and the establishment of research centers. To quote Judge Benjamin Turgano, President of ACSCU, “We recognize that we need to respond to, engage with, and purposefully shape the biosphere to develop a sustainable future for everyone. This demands that we establish multidisciplinary and transdisciplinary research centers and institutes addressing global and national issues. These centers will allow our faculty members, students, and researchers to collaborate in various research. This will provide opportunities to connect with foreign organizations, universities, and institutions who may be interested to collaborate with us and support research initiatives and programs in the field.” This is where I locate our research event these next few days. First, it is located in our difficult post-pandemic world made worse by pseudo-science and the infodemic; second, in our struggle to make sense of our world and in the context of our realization of our agency as academics and citizens of our national community, our world, and our planet; and thirdly, in our vision to make our research projects contributory not only to our vocational and professional growth and institutional development but most importantly, to bring about the vision of the full-life for all.